Estudo de parâmetros relevantes da poluição da água por efluentes de lavanderia e tinturaria industriais em um rio não perene - Santos, Roberto César Mendes Marques dos (2008)
The objective of this study was to evaluate the conditions for modeling the pollution of a river by an effluent from laundry and dying industries. Samples were collected from this treated effluent in the city of Toritama, Pernambuco and in the Capibaribe river before and after the effluent launch. Temperature, pH, color, turbidity, sedimented solids, electrical conductivity, nitrogen (ammonium, nitrite and nitrate), dissolved oxygen, chemical oxygen demand, biochemical oxygen demand, bacteria counting pattern and coliforms (total and thermotolerant) were analyzed. The results of temperature, pH, color, turbidity and sedimented solids from the industrial effluent did not interfere in the water quality of the Capibaribe river. The high electrical conductivity due to the excess of salts in this effluent was one of the parameters responsible for the ecological imbalance. The absence of dissolved oxygen in the treated effluent was one of the factors that did not help the selfdepuration of water. The launch of organic material in the Capibaribe river water with low concentrations of dissolved oxygen was confirmed by the high biochemical oxygen demand. The high bacteriological contamination detected also contribuited for the water pollution. The non sustainability of the river in the period of drought and the difficulty of determining the flow because of dams in the stretch examined, were determining factors that haltered the development of a methodology to identify the type of the mathematic model that should be applied in this study. The disorderly occupation of laundry and dying industries on the banks of the river and the lack of sanitation in the region were the factors that characterized the diffuse pollution. Thus, the construction of a model to simulate the environmental impact of the effluents from the laundry and dying industries was not feasible. The conditions for this investigation did not offer minimal resources needed for the modeling of the River in Toritama. There is a need for a survey of data in small portions of the Rio so that the experimental results can be evaluated and interpreted, targeting the development of a model that could assist in the management of water resources in the region